2021
DOI: 10.1080/21655979.2021.1959221
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA (lncRNA) nuclear enriched abundant transcript 1 (NEAT1) regulates fibroblast growth factor receptor substrate 2 (FRS2) by targeting microRNA (miR)-29-3p in hypertrophic scar fibroblasts

Abstract: Cen (2021) Long non-coding RNA (lncRNA) nuclear enriched abundant transcript 1 (NEAT1) regulates fibroblast growth factor receptor substrate 2 (FRS2) by targeting microRNA (miR)-29-3p in hypertrophic scar fibroblasts,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In addition, they proposed that miR-29a plays the above functions mainly by directly inhibiting the expression of COL1A1 [ 14 ]. Wu et al found that miR-29a-3p was upregulated in hypertrophic scar (HS) tissue and fibroblasts compared with normal skin tissue and confirmed that miR-29a-3p inhibited the proliferation of hypertrophic scar fibroblasts (HSF) and the production of extracellular matrix (ECM) by directly targeting FRS2 [ 15 ]. Yuan et al found that the expression level of miR-29a in mouse scar tissue was significantly downregulated compared with normal skin tissue and proposed that exosomes from miR-29a modified adipose mesenchymal stem cells could reduce excessive scar formation by inhibiting TGF- β 2/Smad3 signal [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they proposed that miR-29a plays the above functions mainly by directly inhibiting the expression of COL1A1 [ 14 ]. Wu et al found that miR-29a-3p was upregulated in hypertrophic scar (HS) tissue and fibroblasts compared with normal skin tissue and confirmed that miR-29a-3p inhibited the proliferation of hypertrophic scar fibroblasts (HSF) and the production of extracellular matrix (ECM) by directly targeting FRS2 [ 15 ]. Yuan et al found that the expression level of miR-29a in mouse scar tissue was significantly downregulated compared with normal skin tissue and proposed that exosomes from miR-29a modified adipose mesenchymal stem cells could reduce excessive scar formation by inhibiting TGF- β 2/Smad3 signal [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of biomedical science, increasing evidences have demonstrated that lncRNAs play a regulatory role in the pathogenesis of various diseases including cancer, myocardial infarction, pulmonary fibrosis and hypertrophic scars by regulating key proteins with competing endogenous (ce) RNAs ( 19-21 ). LncRNA NEAT1 regulates FRS2 by targeting miR-29-3p in hypertrophic scar fibroblasts, thereby exacerbating the pathological process of scar formation ( 22 ). The results of the present study indicated that lncRNA NEAT1 serves an important role in hypertrophic scars by mediating miR-488-3p/COL3A1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…RT-qPCR was conducted on ABI 7500 real-time PCR system (Thermo Fisher Scientific) with SYBR Green kit. GAPDH or U6 was used as an internal control [ 18 ].…”
Section: Methodsmentioning
confidence: 99%